Multi-proxy evidence of late-Holocene paleoenvironmental change at Princessvlei, South Africa: The effects of fire, herbivores, and humans. (1st October 2019) - Cordova, Carlos E.; Kirsten, Kelly L.; Scott, Louis; Meadows, Michael; Lücke, Andreas
Abstract: A multi-proxy approach conducted on a sediment core from a small lake in the Cape Flats (Princessvlei, South Africa), supported by five AMS dates, reveals the paleoenvironments over the last 3900 years. Despite some gaps in the records, phytoliths, diatoms, δ 18 Odiatom, pollen, coprophilous fungus spores, microscopic charred particles (micro-charcoal), and burnt-grass phytoliths, indicate vegetation disturbances caused by climatic changes, anthropogenic influences, fire, and herbivore activity. Pollen spectra indicates a moist period (3600-2600 cal yr BP), which co-occurs with an increase in fires, possibly due to greater biomass fuel loads coupled with the moderate presence of large herbivores. Subsequently, a dry period (2600-1900 cal yr BP) saw a rapid increase of large herbivores probably congregating around the lake, a contention supported also by the occurrence of nutrient-rich waters. This dry period saw reduced fires and a decline of C3 grasses in favor of C4 grasses. The arrival of herders in the Cape after 2000 cal yr BP is not immediately apparent in the multiple records, except for minor vegetation changes and regional fires c. 1200–1400 cal yr BP. However, a more consistent presence of livestock in the immediate area of Princessvlei occurs only after c. 600 cal yr BP, when peak frequencies of coprophilous spores coincide with changes in vegetation composition and occurrence of more eutrophic waters in the lake. The introduction of exotic flora, fire suppression, and a reduction of herding activities, characterizes the period of European settlement (c. 300 BP to present). Highlights: Multiple proxies enhance the reconstruction of environmental changes around a small lake. Multiple proxies help define climatic changes from non-climatic disturbances on vegetation. Critical climatic and cultural changes occurred at Princessvlei (South Africa) in the past 3.9 ka. Native and European disturbance on vegetation and hydrology were considerably different.